2011
DOI: 10.1084/jem.20101499
|View full text |Cite|
|
Sign up to set email alerts
|

Human B1 cells in umbilical cord and adult peripheral blood express the novel phenotype CD20+CD27+CD43+CD70−

Abstract: Human B1 cells consist of CD20+CD27+CD43+CD70− cells bearing a skewed B cell receptor repertoire, and are present in umbilical cord and adult peripheral blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
423
6
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 533 publications
(461 citation statements)
references
References 78 publications
25
423
6
7
Order By: Relevance
“…In mouse models, it was shown that IgM secreted by B1 B cells was responsible for their atheroprotective effect 28. In contrast to their role in mouse studies,28, 33 CD43 + B cells, suggested to resemble B1 cells in mice,15 did not associate with protection against secondary events in our study. Contrasting results have been reported for the association of serum IgM levels with primary cardiovascular events 51, 52, 53.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…In mouse models, it was shown that IgM secreted by B1 B cells was responsible for their atheroprotective effect 28. In contrast to their role in mouse studies,28, 33 CD43 + B cells, suggested to resemble B1 cells in mice,15 did not associate with protection against secondary events in our study. Contrasting results have been reported for the association of serum IgM levels with primary cardiovascular events 51, 52, 53.…”
Section: Discussioncontrasting
confidence: 93%
“…Analysis of the flow cytometry data was performed using Kaluza 1.3 software. We selected viable CD19 + CD3 − lymphocytes, excluded plasmablasts (CD24 − CD38 + ; Figure 1), and gated CD43 + CD27 + cells, which are suggested to resemble B1 B cells 15. Next, we selected unswitched memory cells (CD27 + CD43 − IgD + ) and switched memory cells (CD27 + CD43 − IgD − ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Griffin et al (5) claimed the discovery of a small subset of human CD20 ϩ B cells expressing CD27 and CD43 that recap the functional characteristics of murine B-1 cells. However, controversy has arisen about the nature of these cells, and we recently showed that CD27 ϩ CD43 ϩ B cells are in fact activated cells on their way to plasma cell differentiation (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Each experimental replicate was performed independently with primary human CD34 ϩ cells from different donors. CD34 ϩ cells were isolated with magnetic beads from cord blood samples obtained from the Long Island Blood Service or obtained preisolated from AllCells (11,12). CD34 ϩ cells were put into culture in serum-free VIVO-X 20 medium.…”
mentioning
confidence: 99%